Perceptions of police performance in a rapid-growth community - Huynh, Carol M (International journal of police science & management, 2022)
The purpose of this study was to assess citizens’ perceptions of police performance in a small, rural community that is experiencing rapid population growth. This unique setting differs from other cities and towns because of the pressure that it places on local police to respond quickly and effectively to rapid social changes. A multi-stage random sampling technique was used to gather 380 surveys completed by residents living in Williston, North Dakota during the fall of 2015. The findings revealed that, in general, residents believed that the police were doing a good job addressing community concerns; however, the analysis also revealed that such views were impacted by previous victimization experiences and fear of victimization. In addition, the results indicated that participant sex was significantly related to the perceived ability of police to maintain order on the streets, whereas marital status and the frequency of reading the regional newspaper were significantly related to the perceived ability of police to control crime in the neighborhood.